Developing Students’ Skill in Script Writing for Their Final Project by Applying Guided Writing Task - Khairat, Mutia El; Sariani, Sariani (Humaniora, 2018)
The aim of this research was to develop students? skill in script writing as it was one of the obligations for final year students of English Department, State Polytechnic of Padang (PNP). A qualitative study which was based on the theory of writing task stages highlighted by the expert in this area was taken. The analysis itself was perceived by applying ?Guided Writing Task? stages; Draw and Write Task and Shared Task which resulted in a few written draft scripts. For the triangulation to validate the data, a list of the question was conveyed to the students. The implementation of these two tasks and the students? answer for the questionnaire show that this research has been helpful in improving their script writing skills, particularly on the grammar and organization of how a script should be written.